2013
DOI: 10.7314/apjcp.2013.14.8.4689
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Score to Select Subcentimeter-sized Thyroid Nodules Requiring Ultrasound-guided Fine Needle Aspiration Biopsy in Eastern China

Abstract: Ultrasound-guided fine needle aspiration biopsy (FNAB) is a costly diagnostic item with a low yield in identifying the tiny proportion of nodules that actually represent malignant disease. Our aim through this study was to obtain an ultrasound (US) score for selecting subcentimeter-sized thyroid nodules requiring FNAB in eastern China. Some 248 patients for a total of 270 thyroid nodules less than 1 cm in diameter underwent FNAB and subsequent surgery from January 2006 to March 2012 at our hospital. The clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Similarly, Yoon et al defined a nomogram which is formed of same ultrasonographic features combined with age and nodule size, and showed that it can be used for prediction of malignancies ). An eastern China based recent study also showed that, a scoring system which was developed on the basis of different ultrasonographic features of thyroid nodules can be used for predicting histopathological outcome (Cheng et al, 2013). Not only ultrasonography seems to be a legit tool for predicting malignancy, but also more studies and meta-analyses are needed to define a universally viable set of criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yoon et al defined a nomogram which is formed of same ultrasonographic features combined with age and nodule size, and showed that it can be used for prediction of malignancies ). An eastern China based recent study also showed that, a scoring system which was developed on the basis of different ultrasonographic features of thyroid nodules can be used for predicting histopathological outcome (Cheng et al, 2013). Not only ultrasonography seems to be a legit tool for predicting malignancy, but also more studies and meta-analyses are needed to define a universally viable set of criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide use of high-resolution thyroid ultrasound (US) and fine needle aspiration cytology (FNAC) under US guidance, a number of patients are diagnosed with PTMC without palpable thyroid nodules, which may explain the high incidence during previous years in Eastern China (2,3). The prognosis for PTMC patients is favorable, however, there remains a 1% disease-associated mortality rate, a 5% lymph node recurrence rate and a 2.5% distant metastasis rate (4-7).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have reported that the early diagnosis of thyroid cancer reduced recurrence and mortality (Mazzaferri and Kloos, 2001 less than 10 mm in diameter is particularly important due to high risk of lymph node metastasis and multicentricity (Xie et al, 2009). Currently, there is no any guideline for determining which thyroid nodules for biopsy, especially for micronodules (Cheng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%